Iguanas - Bodden, Valerie (Mankato, Minnesota : Creative Education, Creative Paperbacks, 2017)
A basic exploration of the appearance, behavior, and habitat of iguanas, the North and South American dewlapped reptiles. Also included is a story from folklore explaining why iguanas live in trees.
Booklist, June 2017
Includes index.
2.7
K-3
510L
Center for the Collaborative Classroom Curriculum.
Keywords: Iguanas -- Juvenile literature; Iguanas; Reptiles